2011
DOI: 10.1002/jhm.714
|View full text |Cite
|
Sign up to set email alerts
|

Improving teamwork: Impact of structured interdisciplinary rounds on a hospitalist unit

Abstract: BACKGROUND:Effective collaboration and teamwork is essential in providing safe and effective care. Research reveals deficiencies in teamwork on medical units involving hospitalists.OBJECTIVE:The aim of this study was to assess the impact of an intervention, Structured Inter‐Disciplinary Rounds (SIDR), on nurses' ratings of collaboration and teamwork.METHODS:The study was a controlled trial involving an intervention and control hospitalist unit. The intervention, SIDR, combined a structured format for communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 26 publications
1
91
0
1
Order By: Relevance
“…15,16 SIDR combines a structured format for communication, similar to a goals-of-care form, 17,18 with a forum for daily interdisciplinary meetings. Though no effect was seen on length of stay or cost, SIDR was associated with significantly higher ratings of the quality of collaboration and teamwork climate, and a reduction in the rate of adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 SIDR combines a structured format for communication, similar to a goals-of-care form, 17,18 with a forum for daily interdisciplinary meetings. Though no effect was seen on length of stay or cost, SIDR was associated with significantly higher ratings of the quality of collaboration and teamwork climate, and a reduction in the rate of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, published studies evaluating the benefits of SIDR reflected a pilot study occurring on 2 units. 15,16,19 The current study emphasizes the need to ensure that interventions proven to be effective on a small scale are implemented consistently when put into place on a larger scale. Despite good reliability for assessing teamwork during SIDR across units, domains, and most subteams, we found poor inter-rater reliability for the physician subteam.…”
Section: Discussionmentioning
confidence: 99%
“…Though hospital interdisciplinary rounds aim to increase collaboration and reduce LOS, costs, and readmissions, these rounds do not typically include outpatient care providers. 21 Improved communication and collaboration between social work with both inpatient and outpatient care teams to address nonmedical issues contributing to long stays are likely to improve care and transitions, though rigorous studies examining specific communication models across venues are lacking. This study found that delay in nursing facility placement was the most common reason for prolonged hospitalization for long-stay cases.…”
Section: Discussionmentioning
confidence: 99%
“…As has been demonstrated in other interdisciplinary efforts, increased collaboration among physicians, social workers, discharge planners, and other disciplines may help address current gaps in patient care with regard to LOS. 20,21 Future studies should determine which homebound patients are at highest risk for prolonged hospitalization due to nonmedical factors to help design focused strategies and interventions for this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports that interdisciplinary rounds effectively establish and maintain teamwork, 1,2 improve patient 3,4 and financial 5 outcomes, and increase job satisfaction. 6 …”
Section: Introductionmentioning
confidence: 99%